2018
DOI: 10.1261/rna.062851.117
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and chromatin changes accompanying de novo formation of transgenic piRNA clusters

Abstract: Expression of transposable elements in the germline is controlled by Piwi-interacting (pi) RNAs produced by genomic loci termed piRNA clusters and associated with Rhino, a heterochromatin protein 1 (HP1) homolog. Previously, we have shown that transgenes containing a fragment of the retrotransposon form de novo piRNA clusters in the germline providing suppression of -element activity. We noted that identical transgenes located in different genomic sites vary considerably in piRNA production and classified them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…This is sustained by our ChIP experiments showing that H3K9me3 levels on BX2 OFF are slightly below the H3K9me3 level of piRNA producing states (BX2 ON and BX2 Θ FIG 2D). The same observation can be made for Rhino (FIG 2E) suggesting that Rhino may be already present on the BX2 OFF locus but below the threshold required for piRNA production as suggested by (41). Thus, a locus made of repeated sequences and being likely heterochromatic (H3K9me3, Rhino) is a necessary but not sufficient condition to specify an active piRNA cluster.…”
Section: Discussionsupporting
confidence: 64%
“…This is sustained by our ChIP experiments showing that H3K9me3 levels on BX2 OFF are slightly below the H3K9me3 level of piRNA producing states (BX2 ON and BX2 Θ FIG 2D). The same observation can be made for Rhino (FIG 2E) suggesting that Rhino may be already present on the BX2 OFF locus but below the threshold required for piRNA production as suggested by (41). Thus, a locus made of repeated sequences and being likely heterochromatic (H3K9me3, Rhino) is a necessary but not sufficient condition to specify an active piRNA cluster.…”
Section: Discussionsupporting
confidence: 64%
“…The anti-trimethyl-histone H3 (Lys27) (Millipore, #07-449) antibody was used for ChIP seq experiment. We followed the protocol previously published in Akulenko et al 47 with some modifications. Briefly, ~1000-2000 eggs were bleached, homogenized, and fixed according to optimized ChIP-seq protocol (Supplementary Protocol 2).…”
Section: Chip-seqmentioning
confidence: 99%
“…Originally, the R strain w K devoid of active I-element copies was used for transgenesis. We revealed that the same transgenes, located at different euchromatic genomic loci, form piRNA clusters with various abilities of small RNA production, termed as "weak" and "strong" transgenic piRNA clusters ( Figure 1B) [19,22]. Most importantly, "strong" piRNA clusters are highly enriched in Rhi and produce piRNAs from all transgenic parts, in contrast to "weak" ones, whose piRNAs mostly map to the I-element fragment.Presumably, piRNAs originating from the ancestral I-elements and complementary to the transgenic I-element fragment drive this transformation.…”
mentioning
confidence: 95%